2011
DOI: 10.1029/2010jb007941
|View full text |Cite
|
Sign up to set email alerts
|

Real-time GPS seismology with a stand-alone receiver: A preliminary feasibility demonstration

Abstract: [1] We show the feasibility of a real-time estimation of waveforms and coseismic displacements, within a few centimeters in accuracy, with a stand-alone dual-frequency Global Positioning System (GPS) receiver using a so-called "variometric" approach. The approach is based on time single-differences of carrier phase observations collected at a high-rate (1 Hz or more) using a stand-alone receiver, and on standard GPS broadcast products (orbits and clocks), which are ancillary information routinely available in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 19 publications
(18 reference statements)
1
118
0
3
Order By: Relevance
“…Colosimo et al and Tu et al reported a linear shift in the estimated velocity in epoch difference calculations due to uncorrected atmosphere errors; this shift is stable over a period of around 10 min [1,16]. One to two minutes of velocity data prior to the earthquakes was selected to determine the initial shift by assuming that the time series of the GNSS velocity v(t) can be expressed as:…”
Section: Initial Baseline Shift Correction Of the Integrated System Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Colosimo et al and Tu et al reported a linear shift in the estimated velocity in epoch difference calculations due to uncorrected atmosphere errors; this shift is stable over a period of around 10 min [1,16]. One to two minutes of velocity data prior to the earthquakes was selected to determine the initial shift by assuming that the time series of the GNSS velocity v(t) can be expressed as:…”
Section: Initial Baseline Shift Correction Of the Integrated System Bmentioning
confidence: 99%
“…Epoch-differenced velocity estimation technology, which is based on single-frequency global navigation satellite system (GNSS) observations and satellite broadcast ephemeris, has the advantages of no ambiguity parameters, rapid initialization, high precision, low cost, and rapid turnaround; therefore, it is widely used in earthquake engineering applications, such as real-time earthquake monitoring, early warning, and rapid response [1]. In addition, other studies have focused on GNSS positioning from mass-market receivers for monitoring purposes and real-time earthquake monitoring activities [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Note that ρ T i T j is assumed to be time-invariant and therefore not tagged with the epoch. Note that Q v|c y k is a symmetric matrix and only the upper-triangle elements are listed in Equation (18), similarly for the following (co)variance and cofactor matrices. Assuming totally nt observation types are considered, the number of cross correlation coefficients to be estimated is nt(nt − 1)/2, which can be listed as…”
Section: Cross Correlationsmentioning
confidence: 99%
“…where Q T i1 (k)T i2 (k) is described in Equation (18) and occupies the ((i1 − 1) · ns + 1)th to (i1 · ns)th rows and the ((i2 − 1) · ns + 1)th to (i2 · ns)th columns.…”
Section: Cross Correlationsmentioning
confidence: 99%
“…Nonetheless, it should be pointed out that for Precise Point Positioning (PPP), ambiguity resolution needs a convergence phase that may be as long as 20 min. Fortunately, the Variometric Approach for Displacements Analysis Stand-alone Engine (VADASE) [39] and the Temporal Point Positioning (TPP) [40] are able to overcome this disadvantage. The TPP has been employed in this study.…”
Section: Real-time Kinematic Precise Positioning Performance Of Bds Imentioning
confidence: 99%